Development of Optical Test Strip for Rapid Determination of Trace Arsenic Using Immobilized Gallocyanine - Azah Yusof, Nor; Rashid, Khairunnisa (Asian Journal of Chemistry, 2010)
Irreversible test strip for the determination of arsenic has been developed. It has a rectangular sensing zone containing all the reagents necessary to produce a selective response to arsenic and formed by immobilized gallocyanine inside chitosan membrane. This method offer sensitivity and simplicity in detecting arsenic as no prior treatment or extraction is required. A linear response was attained in the arsenic concentration in the range of 10 to 30 ppm with calculated limit of detection of 0.04 ppm. This method also showed a reproducible result with relative standard deviation of 0.87 % and response time of ca. 5 min. Interference studies showed that Pb(II) and Ni(II) significantly interfered during the determination. The developed sensor has been validated against atomic absorption spectroscopy method and proven comparable.